Leksikal Ekologis dalam Parno Adat Kerinci (Kajian Makna Metafora) - Awliya Rahmi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
This article examines ecological metaphor, a branch and specification of studies in ecolinguistic science (interdisciplinary study between ecology and linguistics). The author observes the traditional Kerinci parno document delivered in a traditional wedding procession. From the collected data, the author finds that the parno contains ecological lexical with metaphorical traits parno. In accordance with the parno context that the author chose, the parno of marriage, the meaning of the metaphor in ecological lexical is the advice from ninik mamak (the custom leders) for the bride and groom. It also conveys the description of single men, and the description of agreement between the couple.